Nuclear issues in the Iran - United States relations: from friends to foes - Rahman, Riki; Othman, Zarina; Ani, Fauziah; Abdullah, Muhaymin Hakim (2020)
Before the 1979 Iranian Islamic Revolution, the US helped Iran in developing its nuclear program, but after the revolution, the US was the main opponent of the nuclear program. The Iran-US good relationship before the revolution was because both countries had mutual interests. Iran needed US assistance to develop its nuclear program, while the US was in need of Iran's supply of oil and made the country as US hegemonic pole and to block the spread of communism of the Soviet Union. When Islamic Revolution took place in 1979, relations between the two countries were at a critical level and indirectly, US interests in Iran were also affected. This turned the Iran-US relations in the opposite phase. However, after Rouhani took over Iran's leadership, Iran-US relations were deemed to be quite good. Unfortunately, when Donald Trump became President of the United States in 2017, Iran-US relation has become uncertain as Trump refused to ratify the nuclear deal. The objective of this article is to clarify Iran-US relations in the context of nuclear issues and to analyse why the relationship changed from friends to foes. It is then elaborated in detail and analysed using a neorealism perspective. This article is qualitative in which primary data is collected through interviews with field experts and report documents as well. Secondary data is collected through library resources and authoritative internet materials. The findings show that the US’s support toward Iranian nuclear before revolution was due to structure or world system, which is the bipolar system, between the US and Soviet Union. After revolution, the US pressured Iran to terminate its nuclear program was due to protect the US hegemony and its ally, Israel. However, Iran still continuing its nuclear program. Iran action to pursue its nuclear program is justified as it is a survival effort as well as to prevent external threats.